2015
DOI: 10.1186/s40885-015-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hypertension and sleep duration: an analysis of the fifth Korea National Health and Nutrition Examination Survey (KNHANES V-3)

Abstract: IntroductionHypertension is a significant risk factor for cardiovascular disease (CVD). The majority of patients, however, cannot easily maintain a healthy blood pressure. Therefore, lifestyle modifications are important and may include getting enough sleep. The purpose of this study was to determine the relationship between sleep duration and hypertension, as defined by the Joint National Committee (JNC) 7 and JNC 8 guidelines.MethodsWe used the data from 6,365 individuals aged ≥ 18 years based on national da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
0
14
0
3
Order By: Relevance
“…hours is associated with a lower risk of uncontrolled hypertension compared to sleep for <7 hours for middle-aged women with hypertension. The short sleep duration has been assumed to be related to the activation of the sympathetic nervous system, 22) and it especially affects nighttime BP levels.…”
Section: Discussionmentioning
confidence: 99%
“…hours is associated with a lower risk of uncontrolled hypertension compared to sleep for <7 hours for middle-aged women with hypertension. The short sleep duration has been assumed to be related to the activation of the sympathetic nervous system, 22) and it especially affects nighttime BP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep duration is associated with adverse health outcomes, such as diabetes, impaired glucose tolerance, hypertension, and obesity. [ 1 4 ] A previous study in Koreans showed that less than 5 hours of sleep is associated with the prevalence of hypertension. [ 4 ] Moreover, the same sleep duration was reported as a risk factor for development of cardiovascular disease (CVD).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that students who sleep less than six hours per night are at significant risk of developing elevated, stage 1 HTN, and stage 2 HTN. Studies have shown that inadequate sleep and poor sleep quality are associated with increased blood pressure [16][17]. In our study, 25.5% (54/212) of students sleep an average of 6 hours or less per night, and we believe that the issue of sleep deprivation is prevalent in other medical schools.…”
Section: Discussionmentioning
confidence: 44%